INFOSEMANTICS. The systematization of the individual way of transforming perception into perspective. - Stefan LAKATOS (Social Sciences and Education Research Review)
The human need for knowledge has existed since our emergence as a species and will always persist, as it can be unequivocally described, both from an evolutionary and a cognitive point of view, as a form of adaptation to an environment. If we consider the fact that the instructions for human adaptation to the environment in which he appeared are encoded in his genetic makeup and, at the same time, the fact that humans possess the natural ability to consciously detect their presence, their actions and the environment in which those are manifesting, then a rigorous examination of how the need for knowledge produces effects at the individual level may offer new perspectives into our collective evolution.